Prevalence and influencing factors of non-suicidal self-injurious behaviour among Chinese college students: a Meta-analysis - TAO Silu; MAO Guoju; XIONG Yi; GUO Mengjia; WU Dongmei (Yixue xinzhi zazhi)
Objective To explore the prevalence and influencing factors of non-suicidal self-injury (NSSI) among Chinese college students and to provide references for effective prevention and intervention measures.Methods CNKI, CBM, VIP, WanFang Data, PubMed, Embase, and Web of Science databases were searched for literatures from inception to December 20, 2024. Two researchers independently conducted literature screening, data extraction, and quality evaluation. Meta-analysis was performed using Stata 17.0 software.Results A total of 36 studies were included. The prevalence of NSSI among Chinese college students was 14.3%[95%CI(12.2%, 16.5%)]. Female [OR=0.83, 95%CI(0.78, 0.89)], neutral personality [OR=0.76, 95%CI(0.69, 0.83)], extroverted personality [OR=0.75, 95%CI(0.68, 0.82)] were the protective factors for the prevalence of NSSI in Chinese college students. Freshman year [OR=1.55, 95%CI(1.22, 1.97)], sophomore year [OR=1.74, 95%CI(1.36, 2.23)], bornin urban or town [OR=1.44, 95%CI(1.26, 1.64)], non-medical colleges or majors [OR=1.50, 95%CI(1.39, 1.61)], negative life events [OR=1.02, 95%CI(1.01, 1.04)], sexual abuse in primary school or earlier [OR=3.14, 95%CI(1.97, 5.02)], depression [OR=1.47, 95%CI(1.33, 1.63)], anxiety [OR=2.20, 95%CI(1.25, 3.87)], fantasies [OR=1.18, 95%CI(1.03, 1.35)], alcohol consumption [OR=1.60, 95%CI(1.40, 1.83)], and feelings of sadness and despair [OR=6.32, 95%CI(2.96, 13.51)] were the risk factors for prevalence of NSSI in Chinese college students.Conclusion The prevalence of NSSI among Chinese college students is high and closely related to a variety of factors. Emotional regulation, mental health support, and early screening for high-risk groups should be strengthened to effectively reduce the prevalence of NSSI.